2009
DOI: 10.1002/jls.20095
|View full text |Cite
|
Sign up to set email alerts
|

Expanding leadership diversity through formal mentoring programs

Abstract: To attract and retain people, it is essential that organizations design and successfully implement programs and processes that develop people and nurture their talents. For those who aspire to a leadership role, the opportunity to engage in mentoring relationships with senior-level leaders is a powerful way to accelerate growth. In the majority of informal mentoring relationships, mentors and protégés share similar racial, gender, and cultural backgrounds. Senior leaders in most large organizations are still p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In informal mentoring, there is no official process, no compensation, training or time-release for those involved [11]. Nevertheless, with well-structured mentoring, the experienced teachers are knowledgeable about providing the required aid, which most inexperienced teachers do not necessarily get [12].…”
Section: Formal Mentoringmentioning
confidence: 99%
“…In informal mentoring, there is no official process, no compensation, training or time-release for those involved [11]. Nevertheless, with well-structured mentoring, the experienced teachers are knowledgeable about providing the required aid, which most inexperienced teachers do not necessarily get [12].…”
Section: Formal Mentoringmentioning
confidence: 99%
“…The results of studies on mentoring in North American and New Zealand universities have found that mentoring plays a significant role in developing women university presidents up the administrative status (Olson & Jackson, 2009;Neale & Özkanlı, 2010). However, research focusing on Asian universities is less conclusive.…”
Section: Mentoringmentioning
confidence: 99%
“…The literature indicated that being mentored is a critical component of leadership opportunities for women (Olson & Jackson, ). Women who are not sponsored or mentored seldom rise above the lower echelons of entry‐level management (Howard & Wellins, .).…”
Section: Women's Attitudes and Leadershipmentioning
confidence: 99%
“…One area of progress within women's leadership that has lagged behind that of men is the role of on‐site mentors (Olson & Jackson, ). Traditional mentoring, whereby an upper‐level manager picks a protégé and oversees his or her progress, has been less available to women (Dreher & Ash, ; Searby & Tripses, ).…”
Section: Introductionmentioning
confidence: 99%